Evaluasi Sistem Akuntansi Pemasukan dan Pengeluaran Kas UMKM di Kecamatan Sedayu - Renya Anjelina; Hasim As’ari (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The research entitled 'Evaluation of the Accounting System for Cash Income and Expenditures for MSMEs in Sedayu District